Investigation of Malondialdehyde (MDA), Homocysteine (Hcy) and C- reactive protein (CRP) in sera of patients with Angina Pectoris - Ahmed Abduljalal Abduljabbar; Parween Abdulsamad Ismail (Al-Mustansiriyah Journal of Science, 2019)
Homocysteine (Hcy) has been considered as an independent risk factor for coronary artery disease (CAD Oxidative stress and free radicals are known to have important roles in the development ofAngina Pectoris. Oxidative stress is present in cardiovascular diseases (CVDs), and hyperhomocysteinemia, an independent risk factor for these diseases, may play a role in inducing production of oxygen free radicals. The aim of this study was to determine a possible relationship between blood serum Hcy levels and lipid peroxidation in patients suffering from Angina Pectoris (AP).To evaluate the possible role of homocysteine (Hcy) in inducing oxidative stress in Angina Pectoris(AP), plasma homocysteine( Hcy), plasma malondialdehyde (MDA) and C reactive protein (CRP) were measured in 60 unstable Angina Pectoris patients, we tested 30 healthy volunteers. Hcy was measured by an enzymatic colorimetric method and MDA, an index of lipid peroxidation, by spectrophotometer. Serum Hcy levels were significantly higher in angina pectories (AP) patients than the controls (23.2±8.0 vs 10.76 ± 2.55 micromol/L; P